2021
DOI: 10.1155/2021/3595064
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Four Different Abutment Screw Torques on Screw Loosening in Single Implant-Supported Prosthesis after the Application of Mechanical Loading

Abstract: Background. The complications of implant-supported prostheses can be classified into mechanical and biological ones, one part of which is associated with screw loosening. This study was aimed to compare the effect of four different abutment screw torque techniques on screw loosening in single implant-supported prostheses following the application of mechanical loading. Materials and Methods. In this experimental study, a total of 40 implants in acrylic blocks (6 × 10 × 20 mm) were mounted perpendicular to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Our results are in agreement with the findings of Kim et al which report that when the number of tightening and loosening (cycles) was increased, the wear also was more severe 19 . Similarly, Ebadian et al when testing screw torque techniques showed that when increasing the insertion torque multiple cycles a decrease in mean abutment screw detorque can be expected 21 …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are in agreement with the findings of Kim et al which report that when the number of tightening and loosening (cycles) was increased, the wear also was more severe 19 . Similarly, Ebadian et al when testing screw torque techniques showed that when increasing the insertion torque multiple cycles a decrease in mean abutment screw detorque can be expected 21 …”
Section: Discussionsupporting
confidence: 93%
“…when testing screw torque techniques showed that when increasing the insertion torque multiple cycles a decrease in mean abutment screw detorque can be expected. 21 One of the limitations of this study was the fact that for microCT we examined only one screw of each group and that a certain intragroup variability can be expected. In vivo conditions have multiple factors (e.g., saliva, wrench key angulation, sealant materials) that were not present in our investigation.…”
Section: Microctmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, research and development of new cancer treatment methods are needed [12][13][14]. New developments in science and technology have significant impact on human health [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and life [30][31][32][33][34][35][36].…”
mentioning
confidence: 99%